Politeness Strategies Used By Ganjar Pranowo and Mahfud MD In the 2024 Presidential and Vice Presidential Candidates Debate Event - Rahma, Naura Alifa; Santoso, Dwi (Journal Corner of Education, Linguistics, and Literature, 2025)
Politeness strategy is a technique used by someone to speak more courteously. Conversations in a daily life and arguments often use polite communication strategies. The 2024 presidential and vice-presidential debates are the debates that are interesting to investigate in this study. This study aims to characterize the politeness strategies employed by Ganjar Pranowo and Mahfud MD during the presidential and vice-presidential debates. This study employed the politeness strategies developed by Brown and Levinson (1978), which categorizes politeness strategies into four types: Off Record (OR), Bald-On Record (BOR), Positive Politeness (PP), and Negative Politeness (NP). The findings of this study show that in the presidential and vice-presidential debates, Ganjar Pranowo and Mahfud MD employ three different kinds of politeness strategies. The most prominent politeness strategy is Positive Politeness (56.5%). Other politeness strategies are Bald-On Record (30.4%) and Negative Politeness (13%). It can be concluded that Ganjar Pranowo and Mahfud MD mostly use Positive Politeness in delivering their speech for presidential and vice-presidential debates.